2004
DOI: 10.1128/mcb.24.23.10223-10235.2004
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Speckle-Associated Protein Pnn/DRS Binds to the Transcriptional Corepressor CtBP and Relieves CtBP- Mediated Repression of the E-Cadherin Gene

Abstract: Previously, we have shown that pinin/DRS (Pnn), a 140-kDa nuclear and cell adhesion-related phosphoprotein, is involved in the regulation of cell adhesion and modulation of the activity of multiple tumor suppressor genes. In the nucleus Pnn is concentrated in the "nuclear speckles," zones of accumulation of transcriptional and mRNA splicing factors, where Pnn is involved in mRNA processing. Alternatively, other roles of Pnn in gene regulation have not yet been established. By utilizing in vitro pull-down assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
64
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 64 publications
4
64
0
Order By: Relevance
“…Recently, PNN has been shown to directly affect the expression of E-cadherin in a CtBPdependent manner in cell culture system (Alpatov et al, 2004), supporting the role of PNN in cell-cell adhesion. Most interestingly, Pnn hypomorphic mice did not display obvious alterations in cell-cell adhesion nor skin barrier formation, as determined by histological analysis and X-Gal penetration assay (data not shown), suggesting that their in vivo phenotypes did not stem primarily from the perturbation of intercellular adhesion.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Recently, PNN has been shown to directly affect the expression of E-cadherin in a CtBPdependent manner in cell culture system (Alpatov et al, 2004), supporting the role of PNN in cell-cell adhesion. Most interestingly, Pnn hypomorphic mice did not display obvious alterations in cell-cell adhesion nor skin barrier formation, as determined by histological analysis and X-Gal penetration assay (data not shown), suggesting that their in vivo phenotypes did not stem primarily from the perturbation of intercellular adhesion.…”
Section: Discussionmentioning
confidence: 76%
“…However, the potential that PNN modulates Wnt signaling is supported by recent data pertaining to its asso-ciation to transcriptional corepressor CtBP. Our laboratory has previously demonstrated that PNN binds to CtBP (Alpatov et al, 2004). CtBP proteins have long been implicated in the regulation of Wnt signaling by direct interactions with a subset of TCF family members to repress the expression of Wnt target genes (Brannon et al, 1999;Chinnadurai, 2002;Valenta et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both modifications have been linked to the regulation of CtBP localization. Furthermore, adenoviral E1A, Epstein-Barr virus oncoprotein EBNA3A, and the nuclear speckle-associated protein Pnn͞ DRS have been shown to sequester CtBP and thereby relieve CtBP-mediated repression (21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%